2021
DOI: 10.3390/agronomy11091756
|View full text |Cite
|
Sign up to set email alerts
|

Soil Test Based Fertilizer Application Improves Productivity, Profitability and Nutrient Use Efficiency of Rice (Oryza sativa L.) under Direct Seeded Condition

Abstract: A field investigation on direct seeded rice (DSR) was carried out in the two consecutive rice growing seasons of 2017 and 2018 at Pantnagar, Uttarakhand, India for the development and validation of soil test crop response (STCR) to fertilizer and for assessing the performance of STCR-treatments as compared to the general recommended dose (GRD) in terms of yield, nutrient uptake and use efficiency, and the economics of DSR. For producing 1 Mg of rice-grain, the required nutrients (N, P, and K) were 2.01 kg, 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 25 publications
(33 reference statements)
1
13
0
Order By: Relevance
“…The higher yield might be associated with proper fertilizer dose determination based on soil tests that can maintain soil fertility and simultaneously can enhance uptake by plants. With similar results to this study, Mittal et al [31] and Singh et al [32] reported that soil test-based fertilizer applications, which were higher than the recommended doses, improved the yield of rice in rice-based systems. However, these studies are conducted in two or three crop-based cropping systems.…”
Section: Yields and Yield Attributessupporting
confidence: 88%
“…The higher yield might be associated with proper fertilizer dose determination based on soil tests that can maintain soil fertility and simultaneously can enhance uptake by plants. With similar results to this study, Mittal et al [31] and Singh et al [32] reported that soil test-based fertilizer applications, which were higher than the recommended doses, improved the yield of rice in rice-based systems. However, these studies are conducted in two or three crop-based cropping systems.…”
Section: Yields and Yield Attributessupporting
confidence: 88%
“…The different NUE indices such as agronomic efficiency of nitrogen (AEN), recovery efficiency of nitrogen (REN), physiological efficiency of nitrogen (PEN), partial factor productivity of nitrogen (PFPN), and internal nitrogen use efficiency (iNUE) were worked ( Peng et al, 2006 ; Meena A. K. et al, 2018 ; Ballester et al, 2021 ; Singh et al, 2021 ) as follows:…”
Section: Methodsmentioning
confidence: 99%
“…The cost of fertilizer (United State Dollar (USD) ha −1 ) for various treatments in the experiment was worked out separately, considering the prevailing prices of fertilizers in USD at the time of their use [37]. Gross return (value of additional yield) was calculated based on the MSP (price for minimum support) of chickpeas by the Indian government during the years of study.…”
Section: Economic Analysismentioning
confidence: 99%